The Effects of an Environmentally Relevant Level of Arsenic on the Gut Microbiome and Its Functional Metagenome. (29th August 2017) - Chi, Liang; Bian, Xiaoming; Gao, Bei; Tu, Pengcheng; Ru, Hongyu; Lu, Kun
Abstract: Multiple environmental factors induce dysbiosis in the gut microbiome and cause a variety of human diseases. Previously, we have first demonstrated that arsenic alters the composition of the gut microbiome. However, the functional impact of arsenic on the gut microbiome has not been adequately assessed, particularly at environmentally relevant concentrations. In this study, we used 16S rRNA sequencing and metagenomics sequencing to investigate how exposure to 100 ppb arsenic for 13 weeks alters the composition and functional capacity of the gut microbiome in mice. Arsenic exposure altered the alpha and beta diversities as well as the composition profile of the gut microbiota. Metagenomics data revealed that the abundances of genes involved in carbohydrate metabolism, especially pyruvate fermentation, short-chain fatty acid synthesis, and starch utilization, and were significantly changed. Moreover, lipopolysaccharide biosynthesis genes, multiple stress response genes, and DNA repair genes were significantly increased in the gut microbiome of arsenic-exposed mice. The genes involved in the production or processing of multiple vitamins, including folic acid and vitamins B6, B12, and K2, were also enriched in arsenic-treated mice. In, addition, genes involved in multidrug resistance and conjugative transposon proteins were highly increased after treatment with arsenic. In conclusion, we demonstrate that arsenic exposure, at an environmentally relevant dose, not only perturbed the communal composition of the gut microbiome but also profoundly altered a variety of important bacterial functional pathways.